Colonial memory and postcolonial Europe : Maltese settlers in Algeria and France - Smith, Andrea L. (New anthropologies of Europe., 2006)
Maltese settlers in colonial Algeria had never lived in France, but, as French citizens, were abruptly "repatriated" there after Algerian independence in 1962. Andrea L. Smith uses history and ethnography to argue that scholars have failed to account for the effect of colonialism on Europe. She explores nostalgia and collective memory; the settlers' limited position in the colony as subalterns and colonists; and selective forgetting, in which Malta replaces Algeria, the "true" homeland, which is now inaccessible, fraught with guilt and contradiction. The study provides insight into race, eth.